Deveres fundamentais na Constituição Federal de 1988: o caso da proteção do meio ambiente - Dozza, Natália (2016)
Although is not as explicit as it should, the current constitutional order is clearly available to be both State and private holders of fundamental rights and duties, although the first group is undoubtedly much trumpeted and protected, both in the courts as in academic circles. Such a gap in the space granted to rights and obligations also creates disharmony in the practical field, to the extent that exacerbated the exercise of rights without the counterpoint ofereceido the duties - related or not - ultimately expand social inequality and other forms of injustice, a situation which is not consistent with the objectives of a Social and Democratic State, as enshrined in the Federal Constitution of 1988. Accordingly, the recognition and application of fundamental duties shown a social imperative, essential to the construction of a just society and materially egalitarian, with strong democratic foundations. Against this backdrop, the environment, the way in which constitutionally assured, stands as both a right and duty, since the guarantee and preservation of a healthy and balanced environment is forecast that extends over time, reach future generations and shows itself indispensable to the prevalence of the human species